Vasopressin: the missing link for preeclampsia? - Sandgren, Jeremy A. (Am J Physiol Regul Integr Comp Physiol, 2015)
Preeclampsia is a devastating cardiovascular disorder of late pregnancy, affecting 5–7% of all pregnancies and claiming the lives of 76,000 mothers and 500,000 children each year. Various lines of evidence support a “tissue rejection” type reaction toward the placenta as the primary initiating event in the development of preeclampsia, followed by a complex interplay among immune, vascular, renal, and angiogenic mechanisms that have been implicated in the pathogenesis of preeclampsia beginning around the end of the first trimester. Critically, it remains unclear what mechanism links the initiating event and these pathogenic mechanisms. We and others have now demonstrated an early and sustained increase in maternal plasma concentrations of copeptin, a protein by-product of arginine vasopressin (AVP) synthesis and release, during preeclampsia. Furthermore, chronic infusion of AVP during pregnancy is sufficient to phenocopy essentially all maternal and fetal symptoms of preeclampsia in mice. As various groups have demonstrated interactions between AVP and immune, renal, and vascular systems in the nonpregnant state, elevations of this hormone are therefore positioned both in time (early pregnancy) and function to contribute to preeclampsia. We therefore posit that AVP represents a missing mechanistic link between initiating events and established midpregnancy dysfunctions that cause preeclampsia.